Comparing of prosecution algorithms of objects - Толстиков, А.Н.; Толстиков, Н.Г. (Eastern-European Journal of Enterprise Technologies, 2010)
The basic categories of algorithms of prosecution were investigated and their comparative analysis was carried out. The basic criteria for a choice of algorithm of prosecution were resulted.